Association between acetaminophen administration and clinical outcomes in patients with sepsis admitted to the ICU: a retrospective cohort study - Sun, Shilin; Liu, Han; Liang, Qun; Yang, Yang; Cao, Xuedan; Zheng, Boyang (Frontiers in Medicine, 2024)
Background Sepsis, affecting over 30 million people worldwide each year, is a key mortality risk factor in critically ill patients. There are significant regional discrepancies in its impact. Acetaminophen, a common over-the-counter drug, is often administered to control fever in suspected infection cases in intensive care units (ICUs). It is considered generally safe when used at therapeutic levels. Despite its widespread use, there’s inconsistent research regarding its efficacy in sepsis management, which creates uncertainties for ICU doctors about its possible advantages or harm. To address this, we undertook a retrospective cohort study utilizing the MIMIC-IV database to examine the correlation between acetaminophen use and clinical outcomes in septic patients admitted to the ICU. Methods We gathered pertinent data on sepsis patients from the MIMIC-IV database. We used Propensity Score Matching (PSM) to pair acetaminophen-treated patients with those who were not treated. We then used Cox Proportional Hazards models to examine the relationships between acetaminophen use and factors such as in-hospital mortality, 30-day mortality, hospital stay duration, and ICU stay length. Results The data analysis involved 22,633 sepsis patients. Post PSM, a total of 15,843 patients were matched; each patient not receiving acetaminophen treatment was paired with two patients who received it. There was a correlation between acetaminophen and a lower in-hospital mortality rate (HR 0.443; 95% CI 0.371– 0.530; p < 0.001) along with 30-day mortality rate (HR 0.497; 95% CI 0.424– 0.583; p < 0.001). Additionally, it correlated with a decrease in the duration of hospitalization [8.4(5.0, 14.8) vs 9.0(5.1, 16.0), p < 0.001] and a shorter ICU stay [2.8(1.5,6.0) vs 3.1(1.7, 6.5); p < 0.05]. Conclusions The use of acetaminophen may lower short-term mortality in critically ill patients with sepsis. To confirm this correlation, future research should involve multicenter randomized controlled trials.